Model Evaluasi dalam Pelaksanaan Event Pendidikan: A Systematic Literatur Review - Sadika, Munadia; Lailatussaadah, Lailatussaadah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to explore research trends on event evaluation models in educational institutions published in online-based journals. This study uses the systematic literature review (SLR) method with the PRISMA approach. The main themes found in this study are the CIPP evaluation model and the Kirkpatrick evaluation model. The originality of this study lies in the presentation of a structured and in-depth literature review, which describes the current state of the evaluation model in the implementation of educational events. The CIPP evaluation model provides a holistic approach to planning, implementing, and measuring outcomes, while the Kirkpatrick model emphasizes more on evaluating the impact of learning and behavioral changes after the event.